On the Impedance Measurement of High Resistivity Materials by Using a Parallel Resistor in Two Probe Arrangement - Mishra R.; Chaitanya P.; Shukla A.; Pandey L.; Thakur O.P.; Parkash O.; Kumar D. (My University, 2025)
Impedance spectroscopy is now an established technique for the study of charge transfer/polarization processes occurring locally as well as at interfaces in various types of material such as polycrystalline ceramics, polymers, composites, ionic conductors, etc. This involves measurement of impedance and various related quantities such as admittance, modulus, permittivity and permeability. The route of analysis of the experimental results is through suitable modelling considered to be adequate for representing the processes. When the resistivity of the material is high, the overall impedance attains very large values falling beyond the measurement range of impedance meters usually available, and the low frequency intercepts in complex impedance plots are not seen. A clever technique, first proposed in our laboratory and later followed elsewhere, is to perform the measurement with a good quality high resistance in parallel to the system. In this paper a detailed analysis of various impedance functions is presented along with the related plots as function of ratios of externally connected resistance and the internal system resistance. As an example, experimental results obtained with SrO.TiO2-2SiO2.B2O3-CoO electronic ceramics are given for demonstrating the technique. © 2013 © 2013 The Indian Ceramic Society.